Conceptualizing Narrative Health and Medicine to Develop Cultural Competence to Improve Communication During the COVID-19 Pandemic - Willis, Kent; Marzilli, Colleen (Advances in Social Sciences Research Journal, 2021)
Narrative health is a technique that healthcare professionals can use to connect with patients. The events of 2020, including the global severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), have identified that patient care is largely dependent upon relationships within the healthcare environment. Relationships in the healthcare environment are established through a trusting exchange between the patient and provider, and one technique to develop this relationship and trust is through narrative health. Narrative health provides the exchange of information between patient and provider in a discussion-like manner, or narrative health. This strategy promotes cultural competence amongst the healthcare professional team and improves communication between the patient and provider. Narrative health is an important concept for healthcare professionals to understand, and narrative health should be a part of any healthcare professional’s toolbox, especially in vulnerable times like the COVID pandemic. The inclusion of narrative health in practice has the potential to improve patient outcomes and empower healthcare professionals and patients.